Regulatory considerations for successful implementation of digital endpoints in clinical trials for drug development - Gül Erdemli; Tina Murphy; Sarah Walinsky (npj Digital Medicine)
Regulatory acceptance of Digital Health Technology (DHT) -derived endpoints can be a long, multifaceted and costly process. Success relies on establishing a global strategy as part of the development program including health authority consultations to ensure alignment with regulatory requirements. In this manuscript, the authors provide stepwise guidance for successful implementation of DHT-derived endpoints in clinical trials for drug development.